The predictive value of revised diastolic dysfunction in outcomes of liver transplantation: A propensity score matching analysis - Bi, Shenghua; Jiang, Yueping; Zhao, Wenjun; Niu, Xiaoyan; Liu, Xuechun; Jing, Xue (Frontiers in Surgery, 2023)
Abstract Background: Diastolic dysfunction (DD), one of the earliest signs of cirrhotic cardiomyopathy (CCM), is included in the revised 2019 CCM criteria. Nonetheless, relevant research regarding the effects of revised DD on post-liver transplantation (LT) outcomes remains limited. Methods: This retrospective study enrolled patients who underwent LT for decompensated cirrhosis, from January 2018 to March 2021. Patients were divided into DD and non-DD groups. Clinical data were collected. Patients were followed up with, for at least 1 year post-LT; cardiovascular adverse events (AEs) and survival status were recorded. Risk factors were identified using 1:2 propensity score matching (PSM), after adjusting for confounding factors. The caliper value was set to 0.02. Results: Of 231 patients, 153 were diagnosed with DD (male, 81.8%; mean age, 51.5±9.5 years). Nineteen patients with DD died within 1 year, post-LT. After PSM, 97 and 60 patients were diagnosed with and without DD, respectively. Patients with DD had longer intensive care unit (ICU) stays, higher perioperative cardiovascular AEs, and higher mortality rates than those without DD. In a multivariate analysis, interventricular septum (IVS), left atrial volume index (LAVI), and potassium levels were independent prognostic factors of perioperative cardiovascular AEs, while a decreased early diastolic mitral annular tissue velocity (e’), increased neutrophil-to-lymphocyte ratio (NLR) and tumor markers were predictors of mortality within 1 year post-LT after PSM (P<0.05). Conclusions: Cardiac DD may contribute to perioperative cardiovascular AEs and mortality post-LT. Clinicians should be aware of decompensated cirrhosis in patients with DD.